The Relationship Between Knowledge And Wife Support With Interest In Using Contraceptives In Men In The Puskesmas Working Area Bermani Ulu Year 2024 - Anita F, Irma; Jumita, Jumita; Putri, Yesi (Journal of Multidisciplinary Research, 2024)
Family planning is one of the methods to reduce the population growth rate. Objective: The purpose of the study was to determine the relationship between knowledge and wife support with interest in using contraceptives in men in the Bermani Ulu Health Centre Working Area in 2024 analytical survey research with a Cross Sectional design. The population of this study was men of childbearing age who visited the Bermani Ulu Health Centre, Rejang Lebong Regency in 2024 from January to April 2024, totalling 328 people, the sample in this study was 180 respondents. Sampling was taken by purposive sampling. The results of the study obtained from 180 respondents most of the respondents (58.3%) had poor knowledge. Of the 180 respondents most respondents (51.7%) the wife supports the use of male contraceptives Of the 180 respondents most respondents (71.1%) the husband's interest is low in the use of male contraceptives. There is a relationship between knowledge and interest in the use of contraceptives in men in the Bermani Ulu Health Centre Working Area in 2024. There is a relationship between wife support and interest in using contraceptives in men in the Bermani Ulu Health Centre Working Area in 2024. It is expected to increase public knowledge about male contraception by increasing health promotion programmes through counselling and health education so that the awareness of men of childbearing age to be willing to use male contraceptives.